(untitled) (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2025)
The bronze naval ram, an essential instrument of Greek and Roman naval warfare, emerged as a significant cultural artifact, permeating diverse aspects of ancient society. While relatively few archaeological examples of rams survive today, their depiction across a broad array of media underscores their symbolic resonance far beyond their utilitarian role in battle. Drawing on textual, archaeological, and iconographic evidence, this paper explores the enduring significance of the ram in both public and private life from the sixth century BCE to the second century CE in the political, economic, and social structures of ancient Greek and Roman societies. Rams were prominently featured in contexts ranging from monumental architecture and funerary art to trade goods and public spectacles, embodying notions of power, military success, and social prestige. Beyond its association with naval dominance, the ram functioned as a visual and rhetorical device employed by individuals across the social spectrum to articulate identity, authority, and community values, while also engaging with themes of masculinity.